TINGKAT KESESUAIAN LAPORAN PENYELENGGARAAN PEMERINTAHAN DAERAH TAHUN 2010 TERHADAP PP NO. 3/2007 - Fitriasari, Debby; Martani, Dwi; Khairurizka, Rahfiani (Prosiding PESAT, 2013)
Despite of the financial statements, the accountability of local government (LG) is also fulfilledthrough LPPD, a LG’s performance reporting on decentralization, job assistance andgovernment administrative tasks. Research on LPPD in Indonesia is still rare. Febriana (2010)and Dalimunthe (2010) conducted a study related LPPD but does not focus on the completenessof the LPPD. Therefore, the purpose of this study is to analyze the compliance of LPPD to PPNo. 3/2007. The compliance level is obtained by comparison the content of the LPPD and thecompliance checklist and then this compliance level will be analyzed using statistic descriptive,the mean difference test and correlation test. With a sample of 25 provinces’s LPPD year 2010,the results show that the average compliance level is 75%. It means that the LG (province) hasnot been submitting all the information in LPPD year 2010 in accordance with the PP No.3/2007. The result of mean different test showed no significant difference in two groups LGbased on these variables: LG’s assets, level of sovereignty, geography position (west or eastIndonesia) and EKPPD value. Moreover, the correlation test results also found no significantcorrelation between the levels of compliance with these variables.